Association between workarounds and medication administration errors in bar-code-assisted medication administration in hospitals. (22nd August 2017) - van der Veen, Willem; van den Bemt, Patricia MLA; Wouters, Hans; Bates, David W; Twisk, Jos WR; de Gier, Johan J; Taxis, Katja; ,; Duyvendak, Michiel; Luttikhuis, Karen Oude; Ros, Johannes JW; Vasbinder, Erwin C; et al.
Abstract: Objective: To study the association of workarounds with medication administration errors using barcode-assisted medication administration (BCMA), and to determine the frequency and types of workarounds and medication administration errors. Materials and Methods: A prospective observational study in Dutch hospitals using BCMA to administer medication. Direct observation was used to collect data. Primary outcome measure was the proportion of medication administrations with one or more medication administration errors. Secondary outcome was the frequency and types of workarounds and medication administration errors. Univariate and multivariate multilevel logistic regression analysis were used to assess the association between workarounds and medication administration errors. Descriptive statistics were used for the secondary outcomes. Results: We included 5793 medication administrations for 1230 inpatients. Workarounds were associated with medication administration errors (adjusted odds ratio 3.06 [95% CI: 2.49-3.78]). Most commonly, procedural workarounds were observed, such as not scanning at all (36%), not scanning patients because they did not wear a wristband (28%), incorrect medication scanning, multiple medication scanning, and ignoring alert signals (11%). Common types of medication administration errors were omissions (78%), administration of non-ordered drugs (8.0%), and wrong doses given (6.0%). Discussion: Workarounds are associated with medication administration errors in hospitals using BCMA. These data suggest that BCMA needs more post-implementation evaluation if it is to achieve the intended benefits for medication safety. Conclusion: In hospitals using barcode-assisted medication administration, workarounds occurred in 66% of medication administrations and were associated with large numbers of medication administration errors.